Top-Down Reform of Islamic Studies: Changing Attitudes among Religious Teachers in Indonesia - Ulum, Miftahul; Romlah, Siti; Fadhilah, Rifqi Zaidan; Mahmudah, Mahmudah; Muazzaroh, Faizatul; Habib, Muhammad Alhada Fuadilah; Binmong, Sorhibulbahree (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This study examines the role of the Religious Education Teachers’ Training Programme as a forum attended by religious education teachers who wish to develop their subject knowledge and be aware of the current aims of religious education. The study examined the effectiveness of this programme in improving teachers’ knowledge of their subject. The training programme was offered every working day for one hour after the end of the teaching and learning process in the form of a lecture followed by a question and answer session. The study material covered eight Islamic sciences, namely the principles of religion (usūl al-dīn), the branches of religion (furū’ al-dīn), exegesis (tafsīr), hadith, Arabic grammar, eschatology, Sufi sciences and moral sciences. Constraints in the implementation of the religious teacher training programme were lack of interest on the part of teachers, who were either unwilling or too busy to attend, while others had other commitments. Efforts were made to overcome these obstacles by adhering to a strict timetable and reminding teachers of the benefits of this programme, in addition to a paid allowance for the extra time.